2005
DOI: 10.1007/s10551-005-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual Responsibility within Organizational Contexts

Abstract: Actions within organizational contexts should be understood differently as compared with actions performed outside of such contexts. This is the case due to the agentic shift, as discussed by social psychologist Stanley Milgram, and the role that systemic factors play in shaping the available alternatives from which individuals acting within institutions choose. The analysis stemming from Milgram's experiments suggests not simply that individuals temporarily abdicate their moral agency on occasion, but that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
1
24
0
1
Order By: Relevance
“…While Jackall advances a world in which people are all too comfortable with a fleeting morality, constantly being renegotiated, Pascal points to the underlying reasons: people's penchant for earthly goods and the absolute reign of self-love. We should also note here that, in the literature about responsibility and its possibility in the corporate context, there is much to support Jackall's pessimistic argument (Bevan and Corvellec 2007;Card 2005;Loacker and Muhr 2009). In fact, an analysis of the literature of organizational power and its impact on the moral responsibility of individual managers seems to suggest that organizations can rob managers of their sense of responsibility (see Carr 1968).…”
Section: Human Relations Marked With the Seal Of Ambiguitymentioning
confidence: 91%
See 2 more Smart Citations
“…While Jackall advances a world in which people are all too comfortable with a fleeting morality, constantly being renegotiated, Pascal points to the underlying reasons: people's penchant for earthly goods and the absolute reign of self-love. We should also note here that, in the literature about responsibility and its possibility in the corporate context, there is much to support Jackall's pessimistic argument (Bevan and Corvellec 2007;Card 2005;Loacker and Muhr 2009). In fact, an analysis of the literature of organizational power and its impact on the moral responsibility of individual managers seems to suggest that organizations can rob managers of their sense of responsibility (see Carr 1968).…”
Section: Human Relations Marked With the Seal Of Ambiguitymentioning
confidence: 91%
“…And, in this evolutionary process, the role that moral luck can play (Velamuri and Dew 2009). The patrimonial bureaucracy described here rests on the principles of managers' behavior, these principles being linked to the demands of the situation rather than any undetectable, intangible ethical content (Card 2005;Norton 1992). This observation is what gives the book its ''disturbing '' nature (Van Maanen 1989, p.…”
Section: Moral Mazes and The Dark Side Of Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this raises questions on how the most devastating financial crisis in recent history could have been caused by what was principally a failure of ethics (Yandle, 2010). Card (2005) has shown that individuals may sometimes abdicate their moral obligations when acting on behalf of an organisation and that there is a systematic erosion of agency over time where there tends to be less accountability for actions taken by the organisation. The author argues that an organisation, with its hierarchy and policies, may reduce an individual"s willingness to accept responsibility for his actions and the individual may therefore be able to act immorally while acting on behalf of the organisation.…”
Section: Literature Review Attitudes Towards Ethicsmentioning
confidence: 99%
“…A study of the contaminating effects of corporate culture on individual moral agency involved scrutinizing the effects of power on individuals within corporations and the impact of bureaucracy on the individual's morality. As Card (2005) argues, one can even witness the abdication or erosion of individual moral responsibility within corporate contexts.…”
Section: Responsibility As a Trait And Role Responsibilitymentioning
confidence: 99%